Weight and type 2 diabetes after bariatric surgery: systematic review and meta-analysis - Buchwald, Henry; Estok, Rhonda; Fahrbach, Kyle; Banel, Deirdre; Jensen, Michael D; Pories, Walter J; Bantle, John P; Sledge, Isabella (The American journal of medicine, 2009)
The prevalence of obesity-induced type 2 diabetes mellitus is increasing worldwide. The objective of this review and meta-analysis is to determine the impact of bariatric surgery on type 2 diabetes in association with the procedure performed and the weight reduction achieved. The review includes all articles published in English from January 1, 1990, to April 30, 2006. The dataset includes 621 studies with 888 treatment arms and 135,246 patients; 103 treatment arms with 3188 patients reported on resolution of diabetes, that is, the resolution of the clinical and laboratory manifestations of type 2 diabetes. Nineteen studies with 43 treatment arms and 11,175 patients reported both weight loss and diabetes resolution separately for the 4070 diabetic patients in these studies. At baseline, the mean age was 40.2 years, body mass index was 47.9 kg/m2, 80% were female, and 10.5% had previous bariatric procedures. Meta-analysis of weight loss overall was 38.5 kg or 55.9% excess body weight loss. Overall, 78.1% of diabetic patients had complete resolution, and diabetes was improved or resolved in 86.6% of patients. Weight loss and diabetes resolution were greatest for patients undergoing biliopancreatic diversion/duodenal switch, followed by gastric bypass, and least for banding procedures. Insulin levels declined significantly postoperatively, as did hemoglobin A1c and fasting glucose values. Weight and diabetes parameters showed little difference at less than 2 years and at 2 years or more. The clinical and laboratory manifestations of type 2 diabetes are resolved or improved in the greater majority of patients after bariatric surgery; these responses are more pronounced in procedures associated with a greater percentage of excess body weight loss and is maintained for 2 years or more.